Serum vitamin D levels in patients with lung metastases - Hanslik, Tomas; Klikovits, Thomas; Soska, Vladimir; Denemarkova, Iveta; Pestal, Adam; Chovanec, Zdenek; Prudius, Vadim; Capov, Ivan; Cervenak, Vladimir; Bilek, Ondrej; Shatokhina, Tetiana; Resler, Jan; et al. (Biomedical papers, 2025)
Background and Aim. Vitamin D deficiency is linked to increased cancer risk and death but the effect of vitamin D substitution on the prognosis of patients with malignant disease is debatable. We aimed to investigate the value of serum vitamin D3 levels in patients with a history of malignancy and confirmed lung metastases.Materials and Method. Serum Vitamin D2 (25-hydroxyergokalciferol) and D3 (25‑hydroxycholekalciferol) levels were measured in 38 patients (28 with and 10 without lung metastases) using high performance liquid chromatography (HPLC). Serum Vitamin D2 + D3 levels of patients with lung metastases were analysed with respect to season, number of metastases, number of malignancies in the history, value according to the ASA (The American Society of Anaesthesiologists) physical status classification, and compared to patients with a history of malignancy without confirmed lung metastasis.Results. Overall, mean serum vitamin D3 levels were significantly higher in summer (summer vs. winter; 85.06 nmol/L vs. 61.01 nmol/L; P=0.013). There was no significant difference in vitamin D3 levels in summer or winter between patients with or without lung metastases. There was also no significant difference in vitamin D3 levels in the summer months between patients with a history of one malignancy versus those with two or more. In winter however, patients with a history of one malignancy had significantly higher vitamin D3 levels (mean, 75.25 nmol/L) than those with two or more malignancies (mean 44.6 nmol/L) (P=0.027). The differences between vitamin D3 levels in patients with ASA 2 and 3 were not statistically significant.Conclusion. Vitamin D supplementation may be advisable for patients with a history of multiple malignancies, particularly during the winter months. However, confirmation in a clinical trial with a larger patient cohort is warranted before firm recommendations can be made.
Keywords: vitamin D; 25(OH)D3; pulmonary metastases; pulmonary resection